Evaluation of techno-functional attributes of starter culture for preparation of Greek- style yogurt - Singh, Jyoti; Mandal, Surajit (Indian Journal of Dairy Science, 2019)
Greek yogurt, a fermented semi-solid product, is derived from yogurt by draining away part of its water and water-soluble components. For industrial production, Greek yogurt can be prepared by concentrating milk by ultra-filtration or addition of milk solids to make up the total solids in final product before fermentation, and then it is referred as Greek-style yogurt. In modern commercial setting, selection of starter cultures can be highly proprietary and result in unique flavour, texture or nutritional profiles. The present study is an attempt to formulate good quality yogurt culture(s) by using different strains of S. thermophilus and Lb. bulgaricus. Co-culturing was done in milk (3% fat, 15%TS) and based on acidification profile, curd setting time, body, texture and culture ratio, 5 ST and 3 LB cultures were selected. Selected cultures were evaluated for technological properties like growth and acidification profile, flavour and CPS production in skim milk with 15 and 25% total solid (TS) at 42Â°C/6h. Acidification and growth profile of selected cultures were comparable at 15 and 25% of TS in skim milk. All five S. thermophilus cultures were positive for acetaldehyde production and galactose fermentation. NCDC 526 and 435 were found with highest galactose utilisation as determined by HPLC. All selected cultures were positive for CPS production. The proteolytic activity of selected cultures (S.thermophilus and Lb. bulgaricus ) were checked in skim milk at 42Â°C/6 h, NCDC 526 found with lowest and I15 with highest proteolytic activity. Cultures were also evaluated for other technologically important attributes like urease activity and dye reduction test. Therefore study of these parameters are important for achieving the best technological performance regarding the selection of cultures to formulate culture combination(s) for preparation of good quality yogurt and Greek-style yogurt at commercial scale.